Chronic Pain in the Elderly: Mechanisms and Perspectives - Dagnino, Ana P. A.; Campos, Maria M. (Frontiers in human neuroscience, 2022)
Chronic pain affects a large part of the population causing functional disability, being often associated with coexisting psychological disorders, such as depression and anxiety, besides cognitive deficits, and sleep disturbance. The world elderly population has been growing over the last decades and the negative consequences of chronic pain for these individuals represent a current clinical challenge. The main painful complaints in the elderly are related to neurodegenerative and musculoskeletal conditions, peripheral vascular diseases, arthritis, and osteoarthritis, contributing toward poorly life quality, social isolation, impaired physical activity, and dependence to carry out daily activities. Organ dysfunction and other existing diseases can significantly affect the perception and responses to chronic pain in this group. It has been proposed that elderly people have an altered pain experience, with changes in pain processing mechanisms, which might be associated with the degeneration of circuits that modulate the descending inhibitory pathways of pain. Aging has also been linked to an increase in the pain threshold, a decline of painful sensations, and a decrease in pain tolerance. Still, elderly patients with chronic pain show an increased risk for dementia and cognitive impairment. The present review article is aimed to provide the state-of-art of pre-clinical and clinical research about chronic pain in elderly, emphasizing the altered mechanisms, comorbidities, challenges, and potential therapeutic alternatives.